The Social Life of Sound - Maalsen, Sophia (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
The Social Life of Sounds argues for the agency of sounds and music and the acceleration of their social lives in the Digital Age. Drawing upon research with composers, producers, record collectors, DJs and record labels, the book problematises the notion of artistic authorship as it is framed in Western systems of property. Acknowledging that 'things' - sounds, samples, and recorded music - and people are co-constituted and that personhood is distributed through things and their reuse, Maalsen makes a case for understanding sound as multibiographical and challenges the possessive individual that is the basis of artistic copyright.